Implementación de biofiltro para remoción sólidos en aguas residuales de procesamiento de almidón yuca, alrededor de comunidad San Pablo Tarugo-Chone, Manabí - Saltos Anchundia, Julián Alejandro (2021)
The aim of this paper study was to remove solids in wastewater from the process of extracting cassava starch, by evaluating the incidence of filter media of sawdust and rice husk with a gravel base and silica sand. The experiment was carried out under an experimental design completely at random, unifactorial, where a total of four treatments were proposed with four repetitions each, obtaining 16 experimental units (16 filters). Samples were taken for each filter once a week for three weeks, and were then taken to the laboratory for turbidity, pH, total suspended solids, total dissolved solids and total solids. In addition, the initial sample of the waste water in its final arrangement was taken to determine its percentage of solids and then to be compared with the final filter implemented and to be able to determine the efficiency of the filter. For the final filter, the treatment (Y2 - H2) was implemented, which had a total bed height of 0,40m and a composition of 0,30m of rice husk, 0,05m of sand and 0,05m of gravel, the same that reached removals of 72,9% turbidity, 51,2% TSS, 45,2% TDS, 61,1% TS and 64,2% BOD removal.